Delegating pricing power to customers: Pay what you want or name your own price? - Florentin Krämer; Klaus M. Schmidt; Martin Spann; Lucas Stich (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
Pay What You Want (PWYW) and Name Your Own Price (NYOP) are customerdriven pricing mechanisms that give customers (some) pricing power. Both have been used in service industries with high fixed capacity costs in order to appeal to additional customers by reducing prices without setting a reference price. In this experimental study we compare the functioning and the performance of these two pricing mechanisms. We show that both mechanisms can be successfully used to endogenously price discriminate. PWYW can be very successful if there is an additional promotional benefit to using PWYW and if marginal costs are not too high. PWYW is a very aggressive competitive strategy that achieves almost full market penetration. NYOP is a less aggressive strategy that can also be used if marginal costs are high. It reduces price competition and segments the market. Low valuation customers are more likely to use NYOP while high valuation customers prefer a posted price seller.
Keywords: D03; D21; D22; D40; L11; M31; 330; Customer-driven pricing mechanisms; Pay What You Want; Name Your Own Price; Competitive Strategies; Marketing; Laboratory Experiment